The back of the napkin : solving problems and selling ideas with pictures. - Roam, Dan, ....- (New York : Penguin, 2008)
A bold new way to tackle tough business problems - even if you draw like a second grader When Herb Kelleher was brainstorming about how to beat the traditional hub-and-spoke airlines, he grabbed a bar napkin and a pen. Three dots to represent Dallas, Houston, and San Antonio. Three arrows to show direct flights. Problem solved, and the picture made it easy to sell Southwest Airlines to investors and customers. Used properly, a simple drawing on a humble napkin is more powerful than Excel or PowerPoint. It can help crystallize ideas, think outside the box, and communicate in a way that people simply "get". In this book Dan Roam argues that everyone is born with a talent for visual thinking, even those who swear they can't draw. Drawing on twenty years of visual problem solving combined with the recent discoveries of vision science, this book shows anyone how to clarify a problem or sell an idea by visually breaking it down using a simple set of visual thinking tools - tools that take advantage of everyone's innate ability to look, see, imagine, and show. The Back of the Napkin proves that thinking with pictures can help anyone discover and develop new ideas, solve problems in unexpected ways, and dramatically improve their ability to share their insights. This book will help readers literally see the world in a new way.